Assessment of Bias in Methodology for Randomized Controlled Trials Published on Implant Dentistry - Herman B. Dumbrigue, DDM;1 Manal I. Al-Bayat, BDS;2 (Journal of Prosthodontics, 2006)
The purpose of this study was to assess randomized controlled trials (RCTs) published on implant dentistry over a 10-year period (1991 to 2000), based on the reporting of control of potential sources of bias in the design methodology.